Engineering Vanadium Pentoxide Cathode for the Zero‐Strain Cation Storage via a Scalable Intercalation‐Polymerization Approach. (27th March 2021) - Wang, Zhiqiao; Tang, Xiaoyu; Yuan, Song; Bai, Miao; Wang, Helin; Liu, Siyuan; Zhang, Min; Ma, Yue
Abstract: The layered V2 O5 cathode exhibits appealing features of multiple electron redox processes and versatile cation‐storage capacities. However, the huge volume respiration induces structural collapse and limits its commercial‐scale deployment. Herein, a scalable water‐bath strategy is developed to tailor the (001) spacing of the bulk V2 O5 from the original 4.37 Å to its triple value (14.2 Å). The intercalated polyaniline (PANI) molecules act as pillars in the V2 O5 interlayer, thus affording the abundant storage sites and enhanced cation diffusivities of Li +, Na +, or hydrated Zn 2+ . Upon various cations (de‐)intercalation, transmission‐mode operando X‐ray diffraction is employed to document the zero‐strain behavior of the PANI‐intercalated V2 O5 . This scalable intercalation‐polymerization strategy, coupled with the compatibility study of the ionic radius and the c ‐lattice for the layered structure, enables the rational engineering of the intercalation‐type cathodes toward facile reaction kinetics. Abstract : Layered V2 O5 is an attractive cathode material that can accommodate various cations, but its real application is limited by the large volume change upon cycling. The polyaniline pre‐pillared host lattice, with highly expanded interlayer spacing, exhibits zero‐strain behavior at fully lithiated, sodiated, or zincated states, and thus can effectively tolerate the electrostatic interaction upon the large ion insertion.